Risk of Falls Among Hospitalized Elderly Patients in a Supra-Tertiary Care Hospital, Thailand - Kaewudom, Chaloemchat; Leethong-In, Mayuree; Ngamlert, Khuanta; Limpawattana , Panita; Ekwuttiwongsa, Rawat (Ramathibodi Medical Journal, 2025)
Background: Falls are an important issue among elderly patients. The chance of falling increases with age, which can affect daily activities, lead to readmission, and reduce quality of life. Objectives: To investigate the risk of falls among elderly patients admitted to an inpatient ward at a supra-tertiary care hospital and to compare fall risk levels of fall risk at various stages of hospitalization. Methods: This was a retrospective descriptive study. All data were obtained from the medical records of 212 older patients admitted between 1 January 2021 and 1 December 2022, at Sriragarind Hospital. The Friedman and Wilcoxon signed rank tests were used to analyze descriptive statistics and variances. Results: The proportion of fall risk at level 1 was 45.75% on the first day of admission, 46.70% during hospitalization, and 58.96% before discharge. The risk of falls was significantly different across the time periods, particularly on the first day of admission compared to during hospitalization and before hospital discharge. Conclusions: The risk of falling increases during hospitalization due to several factors, such as restricted vision and hearing, urinary incontinence, and complications arising during hospitalization. Therefore, a comprehensive fall risk assessment of elderly patients covering all aspects is necessary to prevent the problem from occurring and use the study findings to update the guidelines for preventing falls in older patients.